Natural convection in a porous trapezoidal enclosure with an inclined magnetic field - Saleh, H.; Roslan, R.; Hashim, I. (Elsevier, 2011)
The effect of a magnetic field on steady convection in a trapezoidal enclosure filled with a fluid-saturated porous medium is studied numerically by the finite difference method. The inclined sloping boundaries is treated by adopting staircase-like zigzag lines. The sloping walls are maintained isothermally at different temperatures. The top and bottom horizontal straight walls are kept adiabatic. The results indicate that the heat transfer performance decreases by decreasing the angle of sloping wall. Optimum reducing of the heat transfer rate was obtained for an acute trapezoidal enclosure and large magnetic field in the horizontal direction.